PENENTUAN PENERIMA BEASISWA DENGAN MENGGUNAKAN FUZZY MADM - Apriansyah Putra; Dinna Yunika Hardiyanti (Jurusan Teknik Informatika, 2011)
In every institution especially university, there are a lot of scholarships offered to students. There is a scholarship from the government or from private parties. The scholarship can be gotten if it is appropriate with the rules; including criteria established GPA, parental income, number of siblings, and number of dependents of parents, semester and others. Therefore, not all students who apply to receive scholarships can be granted. It is also necessary to develop a decision support system that can provide scholarship recommendations because there are a lot of criteria and the number of students who apply for the application. To address the selection criteria for scholarship recipients, Fuzzy Multiple Attribute Decision Making (MADM Fuzzy) is used. Fuzzy MADM is a method used to find the optimal alternative from a number of alternatives with certain criteria. Simple additive weighting method (SAW) is one method that can be used to solve fuzzy MADM problems. This method was chosen because this method determines the weights for each attribute, followed by ranking the alternatives who will select the scholarship recipients based on the weights which have been determined to get more accurate results of who will receive the scholarships.